KEPUASAN KONSUMEN PENGGUNA JASA PAKET WISATA DI PT NAIFAH DUTA UTAMA TOUR DAN TRAVEL PEKANBARU - Winda Yuliandari; Firdaus Yusrizal (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The purpose of this research is to know the level of customer satisfaction of Tour package at PT. Naifah Duta Utama Tour & Travel Pekanbaru.This research uses descriptive quantitative method to analyze the problem. The sample used was 30 respondents and the data obtained through questionnaires, observations, and interviews. By using Likert scale as a measuring instrument to determine the length of the interval. Based on the results of research, Customer Satisfaction User Service Tour Packages In PT. Naifah Duta Utama Tour & Travel Pekanabru which consists of four indicators, namely: tangible, emphaty, reability, assurance. The level of customer satisfaction of PT. Naifah Duta Utama Tour & Travel is the highest is on Kemampun to provide services in accordance with the promised and can be on oralkan or reability. Keywords: Level of Consumer Satisfaction, Travel Bureau.